2009
DOI: 10.1074/jbc.a806576200
|View full text |Cite
|
Sign up to set email alerts
|

TRAF6 and MEKK1 play a pivotal role in the RIG-I-like helicase antiviral pathway.

Abstract: On page 30551, Table 1, first column, the experimentally determined values of EC 50 of ER activation for MC, Polysantol, Javanol, and androstenol have been presented with the wrong concentration (mM). The correct concentration is M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…The C-terminal TIM of MAVS has been shown to bind TRAF6 [13], and although previous studies demonstrated that TRAF6 did not function in IFN signaling [13,61], we sought to confirm that the activity of MAVS ∆aa 101-450 was mediated by TRAF3 and not TRAF6. In TRAF6 +/+ and TRAF6 −/− MEFs, the MAVS ∆aa 101-450 construct induced IFNα4 activity, both in the presence or absence of TRAF6, whereas MAVS ∆aa 101-480 did not activate the IFNα4 promoter in either TRAF6 +/+ or TRAF6 −/− MEFs ( Figure 2D), thus ruling out the involvement of TRAF6 in MAVS ∆aa 101-450-driven activity.…”
Section: Traf3 Binds To a Functional Site Within The C-terminus Of Mavsmentioning
confidence: 99%
“…The C-terminal TIM of MAVS has been shown to bind TRAF6 [13], and although previous studies demonstrated that TRAF6 did not function in IFN signaling [13,61], we sought to confirm that the activity of MAVS ∆aa 101-450 was mediated by TRAF3 and not TRAF6. In TRAF6 +/+ and TRAF6 −/− MEFs, the MAVS ∆aa 101-450 construct induced IFNα4 activity, both in the presence or absence of TRAF6, whereas MAVS ∆aa 101-480 did not activate the IFNα4 promoter in either TRAF6 +/+ or TRAF6 −/− MEFs ( Figure 2D), thus ruling out the involvement of TRAF6 in MAVS ∆aa 101-450-driven activity.…”
Section: Traf3 Binds To a Functional Site Within The C-terminus Of Mavsmentioning
confidence: 99%
“…Similar to the TLR3 signaling pathway, TRAF6 and TAK1 play critical roles in the activation of NF-kB and MAPK signaling pathways (10)(11)(12). TRAF6 can also interact with MAPK kinase 1, which in turn contributes to the activation of IkB kinase and MAPKK, leading to activation of the NF-kB and MAPK signaling pathways (13).…”
mentioning
confidence: 99%
“…The IFN type I signalling is mediated through activation of both Janus kinase (JAK) and signal transducers and activator of transcription (STAT) known as JAK-STAT pathway: after receptor activation STAT1/1 homodimers migrate to nucleus and initiate a complex formation with IFN regulatory factor-9 (IRF-9) and interferon stimulated-regulatory elements (ISREs) to induce the expression of many IFN-α/β inducible genes [20]. IFNs production, from host cell, is stimulated via several virus infection, some stress condition and endotoxin exposure resulted in enhancement of the cell response by activation of Jun N-terminal kinasee (JNK) and termed stress-activated protein kinasee (SAPK) [21]. Such events theoretically up-regulates the activity of transcription factor of AP-1 family.…”
Section: Introductionmentioning
confidence: 99%